ASP INJECTIVITY ANALYSIS AS PREPARATION FOR FIELD IMPLEMENTATION - Sugihardjo Sugihardjo (Testing Center for Oil and Gas LEMIGAS, 2018)
This laboratory experiment is a highlight of the preparation of ASP (Alkaline-Surfactant-Polymer Mixture) chemical injection for field implementation to determine the injectivity parameter and the effect of fluid properties change during flow into the porous media. Therefore, the experiments were focus on injectivity which is represented by permeability change. Besides, IFT and viscosity reduction, and also adsorption of injected chemical on the surface of pore throat were also investigated. ASP chemical solution has been prepared for experiments, the mixture consists of 0.3% of Surfactant-A, 1000 ppm Polymer KP and 0.2% alkaline of NaOH. This mixture has been evaluated the bulk properties for instance: IFT, viscosity and other parameter such as: compatibility, thermal stability, phase behavior, and filtration that are suitable for enhanced oil recovery for the target oil field. The next step is to examine the interaction between rock and injected fluid that may change the fluid and rock properties. ASP injection in carbonate rock in this experiment may result in permeability damage and almost totally block the pore throat. Reduction of permeability is very significantly approaching the value of PRF of level 88.76%. The damage could not be revocable after post flush of water that is indicated that the permeability reduction is permanent. Fluid properties of the ASP including IFT and viscosity show that the IFT looks constant and no signifycant change, on the hand the viscosity of the fluid drops down to almost 32.6% from the original. However, the adsorptions are still categorized as normal.